Merleau-Ponty on embodied subjectivity from the perspective of subject-object circularity - Jan Halák (Karolinum Press, 2016)
The phenomenological point of view of the body is usually appreciated for having introduced the notion of the 'lived' body. We cannot merely analyze and explain the body as one of the elements of the world of objects. We must also describe it, for example, as the center of our perspective on the world, the place where our sensing is 'localized', the agens which directly executes our intentions. However, in Husserl, the idea of the body as lived primarily complements his objectivism: the body (Leib) is an objective and mental reality, a 'double unity', as he writes. In contrast, Merleau-Ponty's later considerations of the body in Phenomenology of Perception tend to the idea of a circular relationship between the objective and subjective dimensions of the body - between the objective and the lived. One of the means to overcome the idea of the body as a site of the correlation between two opposite and complementary realms is, for Merleau-Ponty, the philosophical interpretation of an early neurological notion of 'body schema'. Body schema is neither an idea nor a physiological-physical fact, it is rather a practical diagram of our relationships with the world, an action-based norm in reference to which things make sense. In the recently published preparatory notes for his 1953 courses, Merleau-Ponty dedicates much effort to further developing the notion of body schema, and interprets fresh sources that he did not use in Phenomenology of Perception. Notably, he studies various possibilities of how this practical 'diagram' can be de-differentiated (pathology) or further refined (cognitive and cultural superstructures, symbolic systems), which shows the fundamentally dynamic unity of the body. This paper summarizes the basic elements of Merleau-Ponty's 1953 renewed philosophical interpretation of the notion of body schema, while contrasting it to the more traditional understanding of the body in phenomenology and in recent philosophical texts dealing with body schema.